Role of dunaliellasalina extract in competing alzheimer's Disease in experimental animals - FAROUK K. EL-BAZ,; HANAN F. ALY, (International Journal of Pharma and Bio Sciences, 2016)
The purpose of the current work was to study the role of Dunaliella salina extract in ameliorating Alzheimer's disease (AD) in rat brain. Aluminium chloride (AlCl3) was orally administered to male albino rats (100mg/kg/day for six weeks), while, D. salina ethanolic extract (150mg/kg/day for six weeks) was orally administered post AlCl3 treatment. At the end of experiment, AlCl3 treatment markedly increased lipid hydropyroxide (LOOH) and protein carbonyl (PC) levels while, decreased the total protein content (TPC) and total antioxidant capacity (TAC) when compared with normal control rats. As a result of AlCl3 treatment, cerebral cortex showed pyknosis and necrosis of neurons as well as focal cerebral haemorrhage while, hippocampus showed pyknosis and necrosis of pyramidal cells. Treatment of AD rats with D. salina extract decreased the levels of lipid hydropyroxide and protein carbonyl, while it increased TPC and antioxidant status when compared with Al-induced rats. On the other hand, D. salina administered to neurodegenerative rats declared no histopathological changes in cerebral cortex meanwhile, hippocampus showed necrosis of sporadic pyramidal cells. In addition, the cerebral cortex of rivastigmine treated rats showed necrosis of sporadic neurons while, no histopathological changes were observed in hippocampus. The current research clearly indicates the potential of D. salina extract in counteracting the damage inflicted by AlCl3 on rat brain regions.